2014
DOI: 10.9790/2402-08224144
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Composition And Consumers Acceptability Of Bread Produced From Blends Of Soy-Cheese And Wheat Flour.

Abstract: Work on effect of soy-cheese flour inclusion in bread production was investigated. Soy-cheese was produced from carefully sorted and cleaned soybeans and later processed into flour through drying, milling and sifting operations. Bread samples were thereafter produced from blend of wheat and soy-cheese flour using the following blend ratios: 95:5, 90:10, 85:15, 80:20. Bread sample was equally produced from 100% wheat flour which served as control. The bread samples were subjected to proximate and organoleptic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…In the past, other researchers made efforts to incorporate various nutritionally rich ingredients in wheat flour. They (Odedeji et al, 2014;Oyetayo and Oyedeji, 2017;Salazar et al, 2017;Yu and Beta, 2015) reported that in general, the incorporation of herbs improved the nutritional quality of wheat flour by comparatively lowering the moisture content. It is noteworthy that the intermediate moisture content in treatment bread helps prevent the growth of microorganisms and a further reduction in moisture content reduced moulds production, increasing shelf life (Odedeji et al, 2014).…”
Section: Sensory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, other researchers made efforts to incorporate various nutritionally rich ingredients in wheat flour. They (Odedeji et al, 2014;Oyetayo and Oyedeji, 2017;Salazar et al, 2017;Yu and Beta, 2015) reported that in general, the incorporation of herbs improved the nutritional quality of wheat flour by comparatively lowering the moisture content. It is noteworthy that the intermediate moisture content in treatment bread helps prevent the growth of microorganisms and a further reduction in moisture content reduced moulds production, increasing shelf life (Odedeji et al, 2014).…”
Section: Sensory Analysismentioning
confidence: 99%
“…The results of the present study showed a decrease in the carbohydrate content of CWB. In general, variation in carbohydrate contents of the test breads might be attributed to either individual food materials and/or hydrolysis of microflora enzyme that led to the production of other complex carbohydrates from other carbon-containing nutrients as the result of fermentation and combined effect of food fortification (Odedeji et al, 2014). This condition may also be true for other nutrients (Hotz and Gibson, 2007;Odunfa, 1985).…”
Section: Sensory Analysismentioning
confidence: 99%